What Was Helpful Questionnaire (WHQ): Psychometric Properties of a Novel Tool Designed to Capture Parental Perceived Helpfulness of Interventions in Children Requiring Mental Health Inpatient Care - Mourelatou, Ifigeneia; Gaete, Jorge; Fewings, Sandra; Hickie, Oona; Kyriakopoulos, Marinos (Frontiers in Psychiatry, 2019)
Background. Children in mental health inpatient care require multiple treatments. There is not a comprehensive instrument to assess perceived helpfulness of this combination of interventions. Aims. To develop and evaluate the psychometric properties of the What was Helpful Questionnaire (WHQ), a tool designed to capture parental perceived helpfulness of the multidimensional management approach used in inpatient children’s units. Methods. A total of 73 inpatients and their families were included in this study. The WHQ consists of six items exploring the perceived helpfulness of different aspects of care. Demographic and clinical variables were collected on admission and discharge. An exploratory factor analysis using polychoric correlations was performed to assess the item structure of the scale and the Cronbach’s alpha coefficient was used for internal reliability. Associations were assessed using regressions models. Results. WHQ is a unidimensional scale with an internal reliability of 0.77. No associations were identified between WHQ total score and age, gender, Children’s Global Assessment Scale scores change. A strong relationship between the WHQ total score and parental Acorn Satisfaction Questionnaire total score was found. Conclusions. Results add evidence for the validity and the reliability of the WHQ to measure parental perceived helpfulness of interventions offered in inpatient children’s units.